The Influence of the Marketing Mix on the Interests of Customers Using Murabahah's Financing Products - Riri Hanifa; Teuku Muhammad Haqiqi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This study is intended to analyze the effect of product, price, location, and promotion on customer interest in utilizing murabahah financing at Bank Syariah Indonesia KCP Sungai Lilin. This research is a quantitative research method, and data dissemination is done by distributing questionnaires. The sample in this study was 100 respondents, so this questionnaire was distributed to 100 respondents. The technique of collecting data in this study used an accidental random sampling technique, namely the technique of determining the sample by selecting respondents randomly but with certain criteria that must represent the population to be studied. As for the collection of primary data used by researchers, it was obtained from questionnaires distributed to respondents. Furthermore, the collected data were analyzed using multiple regression analysis with the help of the SPSS version 26. The results of this study indicate that product and price partially have a positive and significant effect on customer interest, while location and, promotion do not have a positive and significant effect on customer interest. Simultaneously, the product, price, location and promotion variables together have a positive and significant influence on customer interest in utilizing murabahah financing at Bank Syariah Indonesia KCP Sungai Lilin. Keywords : Product, Price, Location, Promotion, Customer Interest